Re-Imagining Relationships with Space, Place, and Property: The Story of Mainstreaming Managed Retreats in Aotearoa-New Zealand. (20th October 2022) - Hanna, Christina; Cretney, Raven; White, Iain
Abstract: As a nation rapidly progressing managed retreat legislation, we take a historical perspective to identify how the imaginary of retreat evolved in Aotearoa-New Zealand to become mainstream. Tracing the history along a layered reactive-passive-proactive timeline, we reveal how policy experiments and technical advocacy coalitions have advanced different imaginaries of retreat, creating new political spaces for change. We identify the importance of understanding retreat as less of a "policy" and more an attempt to unmake and remake space that has implications for justice and the permanence of land-use and property in an era of dynamic risks.